The time keepers - Richman, Alyson (Union Square & Co., 2024)
"Two women from different worlds, joined by the love of a child displaced by war, discover friendship and healing as their lives intersect with a mysterious wounded Vietnam vet named Jack, who works at the Golden Hours-a watch store that mends timepieces-and maybe even damaged souls"--